Mechanical behavior of inconel 625 at elevated temperatures - De Oliveira, Mauro M.; Couto, Antônio A.; Almeida, Gisele F. C.; Reis, Danieli A. P.; De Lima, Nelson B.; Baldan, Renato [UNESP] (MDPI, 2019)
Inconel 625 is a nickel-based alloy that is mainly used in high-temperature applications. Inconel 625 exhibits an unstable plastic flow at elevated temperatures characterized by serrated yielding, well-known as the Portevin-Le Chatelier effect. The evaluation of the mechanical properties of Inconel 625 at high temperatures is the aim of this work. The tensile tests were executed in temperatures ranging from room temperature to 1000 °C with strain rates of 2 × 10−4 to 2 × 10−3 s−1. The creep tests were executed in the temperature range of 600–700 °C and in the stress range of 500–600 MPa in a constant load mode. The optical and scanning electron microscopes were used for surface fracture observation. In the curves obtained at 200–700 °C the serrated stress-strain behavior was observed, which was related to the dynamic strain aging effect. The yield strength and the elongation values show anomalous behavior as a function of the test temperature. An intergranular cracking was observed for a specimen tensile tested at 500 °C that can be attributed to the decohesion of the carbides along the grain boundaries. The fracture surface of the specimen tensile tested at 700 °C showed the predominance of transgranular cracking with tear dimples with a parabolic shape.
Keywords: Creep; Dynamic strain aging; High temperature; Inconel; Serrated; Tensile test